CTAB-melamine molecular crystals as precursor for synthesis of layered carbon nitride porous nanostructures with enhanced photocatalytic activity for hydrogen production. (December 2021) - Ai, Luchen; Fan, Hai
Abstract: It is still a great challenge to enhance the photocatalytic hydrogen production performance of photocatalysts. Herein, we used a simple two-step method to prepare layered graphitic carbon nitride (g-C3 N4 ) porous nanostructures with much higher surface area by calcination of molecular crystals precursor assembled by hexadecyl trimethyl ammonium bromide (CTAB) and melamine. CTAB was found to act as the soft template and pore forming agent. CTAB and melamine firstly assembled together to form molecular crystals in hydrothermal conditions via electrostatic interaction. Then, after calcination, layered g-C3 N4 porous nanostructures were formed. The as-prepared product exhibited almost 27.5-fold higher photocatalytic hydrogen generation than g-C3 N4, which may be caused by the much higher surface area, faster separation rate of photogenerated hole-electron pairs and the narrowed band gap due to the carbon doping induced by the CTAB. This work provides a facile method for improving the performance of the hydrogen production of g-C3 N4 . Graphical Abstract: ga1 Highlights: ● Layered g-C3 N4 porous nanostructures were successfully prepared. ● CTAB acts as the soft template and pore forming agent. ● CTAB plays a key role for the formation of the layered g-C3 N4 porous structure. ● Layered g-C3 N4 porous nanostructures exhibit much higher surface area. ● CT-CN-2 shows 27.5-fold higher photocatalytic H2 production than g-C3 N4 .